Development of polylactide bead foams with double crystal melting peaks. (9th July 2015) - Nofar, Mohammadreza; Ameli, Aboutaleb; Park, Chul B.
Abstract: In this study, we report the development of polylactide (PLA) bead foams with a double crystal melting peak structure. PLA bead foams with 3- to 30-fold expansion ratios and average cell sizes ranged from 350 nm to 15 μm were prepared. We found that the PLA's foam structure was significantly affected by the amount of perfected crystals (that is, crystals with a high melting temperature) generated during CO2 saturation. The structure was also affected by crystals with a low melting temperature that formed during foaming and cooling. Various CO2 pressures further influenced the crystallization kinetics of the crystals with a high melting temperature during the saturation. At various pressures, different crystallization kinetics also significantly affected the PLA foam's cell morphology and its uniformity. At a high saturation pressure, the increased content of dissolved CO2 in the PLA promoted the cell nucleation rate through the increased degree of thermodynamic instability. On the other hand, at high pressures, small-sized perfect crystals were induced as high-melting peak crystals. Thus, the heterogeneous cell nucleation around these crystals was further improved, which also caused the generation of a more uniform foam structure. Moreover, this study introduces this bead foam technology as an innovative new way to produce nanocellular foam products. Graphical abstract: Highlights: Expanded PLA (EPLA) bead foams are developed with a double crystal melting peak. Generation of double crystal peak significantly improves PLA's foaming properties. CO2 pressures influenced the kinetics of the high-melting temperature crystals. The high-melting peak crystals enhanced the PLA's cell nucleation/foam expansion. Nanocellular foam products can be produced by this bead foaming approach.